Value Analysis of Preoperative Peripheral Blood Markers in the Identification of Benign From Malignant Parotid Gland Tumors - Zheng Ye; Hui Dong; Fuyong Sui (International Dental Journal, 2025)
Objectives: To assess the value of preoperative peripheral blood inflammatory and nutritional parameters in distinguishing between benign and malignant parotid gland tumors. Methods: A retrospective analysis was conducted on 79 patients with malignant parotid gland tumors and 79 patients with benign parotid gland tumors who were treated at the Second Hospital of Dalian Medical University from January 2015 to December 2024. Preoperative levels of total protein (TP), prealbumin (PA), albumin (Alb), albumin-to-globulin ratio (AGR), apolipoprotein A1-to-apolipoprotein B ratio (ApoA1/ApoB), and platelet-to-lymphocyte ratio (PLR) were compared between the malignant and benign tumor groups. The diagnostic value of these parameters in differentiating between benign and malignant parotid tumors was evaluated. Results: The ApoA1/ApoB ratio and PLR were significantly higher in the malignant tumor group compared to the benign tumor group (P < .05). Conversely, TP, Alb, PA, and AGR were significantly lower in the malignant tumor group than in the benign tumor group (P < .05). Binary logistic regression analysis identified TP, PA, AGR, and ApoA1/ApoB as independent risk factors for parotid malignancy (P < .05). The optimal cut-off values for diagnosing parotid malignancy were 65.75 for TP, 248.46 for PA, 1.55 for AGR, and 1.45 for ApoA1/ApoB. Conclusions: Preoperative peripheral blood inflammatory and nutritional markers may serve as valuable indicators for differentiating between benign and malignant parotid gland tumors, providing a potential adjunctive diagnostic tool. However, further large-scale studies are required to validate these findings.